2010
DOI: 10.1063/1.3460098
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of SrTiO3/SiO2/Si Interfaces at Intermediate Oxygen Pressures

Abstract: The thermal stability of epitaxial SrTiO3 thin films grown by molecular-beam epitaxy on Si (001) has been studied using x-ray diffraction (XRD), optical microscopy (OM), scanning electron microscopy (SEM), and thermodynamic calculations. Our studies focus on the stability of the SrTiO3/Si structures under the conditions typically employed in the pulse laser deposition (PLD) growth of complex metal oxide heteroepitaxy on Si. We observe additional Bragg peaks in thermally treated SrTiO3 buffered Si structures, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…For compositions 10-40%, the symmetric 2θ−θ scan ( become amorphized and that a thin (~1.5 nm) SiO x layer has also formed. The reason for the loss of crystallinity in the undoped STO layer are still unclear and may be due to either preferential amorphization as a result of the TEM sample preparation [40] or to reaction of the thin STO layer with silicon forming silicates and silicides [41][42].…”
Section: Methodsmentioning
confidence: 99%
“…For compositions 10-40%, the symmetric 2θ−θ scan ( become amorphized and that a thin (~1.5 nm) SiO x layer has also formed. The reason for the loss of crystallinity in the undoped STO layer are still unclear and may be due to either preferential amorphization as a result of the TEM sample preparation [40] or to reaction of the thin STO layer with silicon forming silicates and silicides [41][42].…”
Section: Methodsmentioning
confidence: 99%
“…13 The final slow cooling of the multilayer stack at 1°C / min in ϳ400-500 Torr O 2 is also conducive to the optimal oxygenation of the NSMO layer. Interestingly, before the CeO 2 and BTO depositions, it was found that the 3°C / min ramp rates yielded better samples than a 1°C / min or 2°C / min ramp rate, suggesting that minimizing the time the sample spent at high temperature ͑avoiding reactions͒ is an important factor due to the potential for interfacial reactions mediated by the silicon dioxide decomposition interfacial reaction SiO 2 +Si → 2SiO͑g͒.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike vdW materials, which are fundamentally at a disadvantage due to the inevitability of the weak vdW interaction with the substrate, complex oxides are able to form chemical bonds with the substrate at high temperatures. 17 Therefore, complex oxides promise a stronger adhesion to the substrate than 2D materials. For example, using direct wafer bonding (DWB), single crystal complex oxides such as LiNbO 3 have been shown to be able to bond directly onto other substrates like Si 18 20 to create submicron thick MEMS resonators.…”
Section: Introductionmentioning
confidence: 99%